The assessment of Ki-67 as a prognostic marker in neuroendocrine tumours: a systematic review and meta-analysis. Issue 7 (17th December 2015) - Richards-Taylor, Sebastian; Ewings, Sean M; Jaynes, Eleanor; Tilley, Charles; Ellis, Sarah G; Armstrong, Thomas; Pearce, Neil; Cave, Judith
Abstract : Introduction: Gastroenteropancreatic neuroendocrine tumours (GEP NETs) are classified according to tumour mitotic count or Ki-67 labelling index (LI). Aim(s): To systematically review articles reporting the prognosis of patients by Ki-67 LI and thereby improve the ability of clinicians to prognosticate for their patients. Method: 265 abstracts were identified relating Ki-67 and survival. After exclusion criteria were applied, 22 articles remained. Articles were excluded if they described non-human specimens, were non-English language, published prior to 2000, reported non-GEP NETs, reported subgroups selected by treatment modality or included <20 cases. Random-effects meta-analysis was used to combine studies to estimate survival proportions. Results: Authors used varied methods in which to present 5-year survival, with often limited survival information. This reduced the number of studies that could be included in the meta-analysis. 5-year survival for patients with grade 1 and 2 GEP NETs were estimated to be 89% (95% CI 85% to 92%, m=12 studies, n=977 participants) and 70% (95% CI 62% to 79%, m=9, n=726), respectively. Using an alternative grade 1/2 boundary of 5%, 5-year survival rates for Ki-67≤5% and 5–20% were estimated as 89% (95% CI 84% to 94%, m=7, n=654) and 51% (95% CI 44% to 59%, m=4, n=183), respectively. For Ki-67>20%, 5-year survival was estimated to be 25% (95% CI 12% to 38%, m=10, n=208). Conclusions: Standardisation of grade boundaries has allowed us to combine data from multiple studies and amass a body of evidence linking Ki-67 and survival.